Igrejas do Modernismo e Vaticano II : espaços de (comum) união. - Sonda, Laíde Inez (2020)
The building-churches manifest a visible and invisible reality. The church made of stone is a symbol of the church made of people who gather to celebrate and like the stones of the building, form a unity in Christ. This unity is expressed in the organization of spaces, especially inside the church where the Catholic church’s liturgical actions take place. The way in which the community is disposed in the space also manifests the level of involvement, of participation in actions that are developed from poles or centralities: altar, ambo, chair of the presidency, baptismal font. The organization of informal spaces from the beginning of Christianity, favored the assembly, the community meeting and participation. Over time, they were replaced by spaces with a clear separation between clergy and faithful. The celebration, a community act, became an action of the elders, carried out alone, without the participation of the community and the poles lost their centrality and were overshadowed by the excess of decorativism and images. The Liturgical Movement emerged in the Church in the early 1900s and the Second Vatican Ecumenical Council was held between 1962-1965. These were two key moments in the Church that promoted the general reform of the liturgy in order to return to the meaning of community celebration, the meaning of being Church. The spaces have also undergone countless changes under the same umbrella: promoting participation, giving back to the celebratory poles their centralities, promoting noble simplicity more than sumptuousness. In the analysis of the churches, aspects of modern architecture, specific characteristics and the values a re presented from the perspective of each architect: Hans Broos, Paulo Archias Mendes da Rocha, Lina Bo Bardi, João da Gama Filgueiras Lima, Francisco Segnini and Joaquim Barretto. We look more carefully at the analysis of spaces as inducers of participation and communion and symbolically configured to show the communion of all in Christ, a guaranteed presence in the celebratory assembly.